Indications for Human Albumin Infusion in a Neonatal Population: A Single Center Experience - Degirmencioglu, Halil; Say, Birgul; Oguz, Serife Suna (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: To evaluate the indications for human albumin infusion, the suitability of albumin infusion in neonatal intensive care units and neonatal outcomes after human albumin administration. Study Design: Infants who had hypoalbuminemia (HAlb) (albumin level <20 g/L) and were given albumin infusion at any time during hospitalization between December 2012 and December 2013 were included in the study. Mortality (group 1 (alive), group 2 (died during hospitalization)) and morbidities were recorded. Demographic properties were assessed retrospectively. Results: 38 neonates required HA transfusion therapy 61 times during the study, 89.5% were premature birth. 9 (23.7%) of 38 patients underwent major surgery. Group I =survived and are currently alive (n=22, 58%), Group II= died during hospitalization (n=16, 42%). In the groups, aspartate aminotransferase, creatinine and albumin levels were significantly different before and after infusion. Conclusion: The value of HA in the clinical setting continues to be controversial and well-designed guidelines for its use in NICUs should be established for the neonatal period.